The Effectiveness of the Creative-Scientific Decision Making Skills (CSDMS) Model to Practice Creative Thinking Skills and Decision Making Skills - Asister Fernando Siagian; Muslimin Ibrahim; Zainul Arifin Imam Supardi (IJORER : International Journal of Recent Educational Research, 2022)
This study aims to produce an effective Creative-Scientific Decision Making Skills (CSDMS) learning model that can be used in training students' creative thinking skills and decision-making skills. This study uses the One Group Pretest – Posttest design. Data were analyzed descriptively with pre-test and post-test data analysis using paired t-test in limited trials, and independent t-test in broad trials. It was concluded that the CSDMS model was declared valid both in terms of content validity and construct validity in order to improve students' creative thinking skills and decision-making skills. The results showed that the CSDMS model met the effective criteria in terms of the average n-gain of creative thinking skills in the high category and decision-making skills in the medium category, consistent with the average n-gain not significantly different in each university. It was concluded that the CSDMS model was found to be effective in improving students' creative thinking skills and decision-making skills.